The (Im)Possibility of Persistence? – Najm al-Dīn al-Ṭūfī’s (d. 716/1316) Atomistic Argumentation for the Probative Value of istiṣḥāb al-ḥāl - Kurnaz, Serdar (Islamic law and society, 2024)
Istiṣḥāb al-ḥāl, the presumption of the persistence of a state or ruling, is a disputed source within Islamic jurisprudence. For some scholars, it is one of the main sources of Islamic law. Many juristic principles are based on istiṣḥāb. The Hanbali scholar al-Ṭūfī (d. 716/1316) follows this idea in Sharḥ Mukhtaṣar al-Rawḍa and holds that istiṣḥāb is the fourth source of law after the Quran, Sunna, and Consensus. Al-Ṭūfī argues for the validity of istiṣḥāb with regard to a physical theory in kalām known as atomism. He discusses the possibility of continuation in existence. In his view istiṣḥāb is based on the principle that persistence/continuation (baqāʾ) is an accident (ʿaraḍ) that is not re-created in each moment in contrast to kalām atomism, which postulates that accidents are re-created constantly. This article presents al-Ṭūfī’s original approach to the validity of istiṣḥāb that guarantees the continuous existence of a state and ruling.